Analisis Rasio Profitabilitas dan Rasio Likuiditas terhadap Kinerja Keuangan pada Perusahaan Maskapai Penerbangan yang Terdaftar di BEI Tahun 2020-2022 - Yogi Setya Dharmajati; Nurul Hidayah; ⁠Iin Wijayanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The financial performance of airline companies is influenced by natural and non-natural situations and conditions. In 2020-2022, airline companies registered on the IDX experienced unstable financial conditions, caused by non-natural disasters, namely the Covid-19 pandemic. This has an impact on the stability of the airline company's financial performance. This research aims to analyze the financial performance of airline companies based on profitability ratios (net profit margin, return on assets, return on equity) and liquidity ratios (current ratio, quick ratio, cash ratio). The data used in this research is secondary data, while this research uses quantitative descriptive data analysis methods. The results of the research show that the company's NPM, ROA and ROE ratios tend to be negative values, so that the ratio results are below the profitability ratio standard, while the company's current ratio, quick ratio and cash ratio are also below the liquidity ratio standard. Obtaining a ratio that is below standard indicates the company's financial performance is poor and unsatisfactory.